Karakteristik Marshall Campuran AC–WC yang Menggunakan Abu Tempurung Kelapa dan Abu Cangkang Sawit Sebagai Pengganti Filler - Putra, Rio Syaenanda; Ramadhani, Ramadhani; Haruno, Hardayani (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
This research discusses the utilization of palm kernel shell ash and coconut shell ash as filler substitutes in Asphalt Concrete - Wearing Course (AC - WC) mixtures. This research uses a laboratory test method, which is to find the results of using palm kernel shell ash and coconut shell ash as filler additives in the Asphalt Concrete - Wearing Course (AC - WC) layer. This research was conducted through the Marshall test to determine the stability and flow (melt) values of the test samples. Marshall properties refer to the maximum load that an asphalt mixture can withstand, even at its melting point. The flow rate is expressed in kilograms. Marshall parameters include VIM (Void in Mix), research-related data collection in the form of references and supporting equipment to study asphalt pavement mixtures to study the effect of temperature changes. The Marshall test research was then continued by collecting information about the materials used in the laboratory experiments used in the test specimens. VFA (Void Filled With Asphalt), VMA (Void In Mineral Aggregate), Stability, Flow and Marshall Quotien (MQ) values.